3D Simulation Study on Thermal Behavior and Thermal Stress of Lithium‐Ion Battery. Issue 2 (25th December 2022) - Zhai, Qingwei; Xu, Xiaobin; Kong, Jizhou; Liu, Mingguang; Xu, Peng; Heidarshenas, Behzad; Wang, Qianzhi; Zhou, Fei; Wei, Hongyu
Abstract : Temperature and thermal stress are crucial factors affecting the working performance and thermal safety of lithium‐ion batteries (LIBs). During the discharge process of the battery, the temperature increases. The thermal expansion stress caused by the entropy heat and the ohmic heat can lead to the battery's lifetime reduction and even thermal safety issues. Herein, based on the coupled electrochemical model, the LIB's thermal behavior and thermal stress distribution at a 1C discharge rate are simulated and analyzed. The results show that the temperature distribution inside the battery is mainly affected by the heat exchange surface and the position of the tabs during the discharging process, in which the localized high‐temperature region occurs in the positive tab. The thermal stress inside the battery enhances rapidly at both the beginning and end of the discharging process while increasing slowly in the middle. Abstract : Temperature and thermal stress are crucial factors that affect the working performance and thermal safety of lithium‐ion batteries (LIBs). According to a coupled electrochemical–thermal–mechanical model, the internal temperature and thermal stress distribution of the cylindrical battery at the discharge rate of 1C are simulated and analyzed. This model can be developed for the thermal management and internal structure design of LIBs.